2017
DOI: 10.1186/s13058-016-0793-2
|View full text |Cite
|
Sign up to set email alerts
|

18FDG-PET/CT for predicting the outcome in ER+/HER2- breast cancer patients: comparison of clinicopathological parameters and PET image-derived indices including tumor texture analysis

Abstract: BackgroundThis study investigated the value of some clinicopathological parameters and 18 F-fluorodeoxyglucose-positron emission tomography/computed tomography (18FDG-PET/CT) indices, including textural features, to predict event-free survival (EFS) in estrogen receptor-positive/human epidermal growth factor receptor 2-negative (ER+/HER2-) locally advanced breast cancer (BC) patients.MethodsFDG-PET/CT indices and clinicopathological parameters were assessed before neoadjuvant chemotherapy (NAC). After completi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 28 publications
6
51
1
Order By: Relevance
“…Groheux et al . found that high SUV, including SUVmax, SUVmean and SUVpeak, were associated with shorter EFS 8 . However, homogeneity was not predictive for EFS (HR = 2.27, P = 0.07).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Groheux et al . found that high SUV, including SUVmax, SUVmean and SUVpeak, were associated with shorter EFS 8 . However, homogeneity was not predictive for EFS (HR = 2.27, P = 0.07).…”
Section: Discussionmentioning
confidence: 89%
“…Heterogeneity is therefore a prognostic factor 5 and may be a predictor of treatment failure and drug resistance, including endocrine resistance. Recently, 18F-FDG PET/CT is used to evaluate tumor heterogeneity by tumor textural information and glucose uptake 6 8 . It is an easy and non-invasive method to assess heterogeneity compared with genomic approach by biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…The imaging findings on 18 F-FDG PET/CT in patients with breast cancer have been correlated to tumor type, size, grade, receptor expression, and nodal metastases with variable success. [ 14 15 ] The present study aimed to see if the changes in 18 F-FDG PET/CT could reflect the tumor biology as represented by the molecular subtype. The study population was fairly uniform that all patients had locally advanced infiltrating duct breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that FDG PET/CT can have a significant impact on the therapeutic management; however, information concerning its utility for a long-term prognostic stratification, when compared with CI, is limited 48. In particular, there is no consensus about the best PET-derived parameters to predict patients’ prognosis and/or survival 76. First published studies were focused on the prognostic value of SUV max , without testing other PET parameters 76.…”
Section: Feasibility and Patient Outcomesmentioning
confidence: 99%
“…In particular, there is no consensus about the best PET-derived parameters to predict patients’ prognosis and/or survival 76. First published studies were focused on the prognostic value of SUV max , without testing other PET parameters 76. More recently, other PET-derived parameters such as metabolic tumor volume (MTV) and total lesion glycolysis have demonstrated to potentially improve risk stratification, in this specific subtype of breast cancer patients 7780…”
Section: Feasibility and Patient Outcomesmentioning
confidence: 99%